Strategi Pembelajaran Online Pada Mata Pelajaran Informatika di SMA Negeri 3 Jeneponto - Firdha Sabrina (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
During the Covid-19 pandemic, face-to-face learning in schools was shifted to online learning by the government to prevent the spread of the coronavirus. This is a challenge for teachers in online education, one of which is choosing and implementing appropriate learning strategies in particular situations, namely online learning. The purpose of this study is to describe the learning strategies applied by the teacher, their implementation, and the obstacles in online education in informatics at SMA Negeri 3 Jeneponto. This research is qualitative research and a type of qualitative descriptive research. This research was conducted at SMA Negeri 3 Jeneponto, with the subject of the study being the informatics subject teacher. Data collection techniques through observation, interviews, and documentation. The data analysis of this research consisted of data reduction, data presentation, and conclusion drawing/verification. The results show that teachers use the WhatsApp application and utilize WhatsApp groups as an online informatics teaching and learning class; teachers apply exposition strategies and individual learning strategies and assign assignments to informatics subjects at SMA Negeri 3 Jeneponto. The application of a teacher's online learning strategy focuses on delivering theory and giving lessons to students, while the implementation of online informatics practice still cannot be applied. The teacher found several internal and external obstacles during the online learning period of informatics at SMA Negeri 3 Jeneponto.